Feature Selection of the Combination of Porous Trabecular with Anthropometric Features for Osteoporosis Screening - Enny Itje Sela; Sri Hartati; Agus Harjoko; Retantyo Wardoyo; Munakhir Mudjosemedi (International Journal of Electrical and Computer Engineering (IJECE), 2015)
This study aims to select the important features from the combination of porous trabecular pattern with anthropometric features for osteoporosis screening. The study sample has their bone mineral density (BMD) measured at the proximal femur/lumbar spine using dual-energy X-ray absorptiometry (DXA). Morphological porous features such as porosity, the size of porous, and the orientation of porous are obtained from each dental radiograph using digital image processing. The anthropometric features considered are age, height, weight, and body mass index (BMI). Decision tree (J.48 method) is used to evaluate the accuracy of morphological porous and anthropometric features for selection data. The study shows that the most important feature is age and the considered features for osteoporosis screening are porosity, vertical pore, and oblique pore. The decision tree has considerably high accuracy, sensitivity, and specificity.